Integration of thermochemical energy storage in concentrated solar power. Part 2: Comprehensive optimization of supercritical CO2 power block. (April 2020) - Tesio, U.; Guelpa, E.; Verda, V.
Highlights: High-temperature thermochemical energy storage for Concentrated Solar Power. High number of combinations analyzed through HEATSEP method and superstructure. Multi-objective optimization of complete Calcium-Looping plant. Novel layouts designed for indirect integration of supercritical CO2 cycles. Discontinuous Pareto curve obtained because of plant layout changes. Abstract: Among the various options of Thermo-Chemical Energy Storage, Calcium-Looping represents a promising alternative for Concentrated Solar Power plants, thanks to high operating temperatures, high energy density and absence of thermal losses. Finding the most suitable power cycle for this system is a task that has still to be solved and is not trivial because it consists in a complex process synthesis problem. From a preliminary analysis (Part 1), supercritical CO2 cycles results to be the most promising option. In the present work, the integration of this power block (pilot plant size, 2 MWe ) is deeply investigated through a comprehensive analysis. Numerous thermal cycle layouts are considered and two options for the power block thermal feeding are assumed. The HEATSEP methodology (comprising genetic algorithm, pinch analysis and bisection) is adopted to optimize both components operating conditions and heat transfer processes in the discharging phase. The plant section devoted to the charging process is optimized and dimensioned taking into account the transient operation. Thanks to the complex problem structure developed, the algorithm is free to find the most suitable configuration between a huge set of feasible combinations. Both energy and economic optimizations are performed for the complete plant and, being in contrast between them, a multi-objective optimization is executed. The independent variables influence on the resulting configuration is assessed and intermediate layouts obtained from the Pareto curve are commented. Carbonator inlet temperature of reactants are observed to increase with plant efficiency. The maximum efficiency (21%) is obtained with the most complex power block (recompression, intercooling and reheating) exchanging heat directly on the carbonator wall. Less performing discharging processes are cheaper but determine higher costs of charging sections; the resulting effect is positive and the integration of simpler power blocks results economically convenient. A power cycle with single intercooling and thermal feeding performed on the carbonator outflows is the result of economic optimization (efficiency equal to 16.3%). The algorithm gives precedence to power block thermal feeding and then to reactants preheating. Novel plant layouts are designed for these configurations and data useful for further investigations are provided in the last part of this work.